ANALISIS BREAK EVEN POINT SEBAGAI PERENCANAAN LABA USAHA KELOMPOK TANI SARI BUAH KELURAHAN LEMBAH SARI KECAMATAN RUMBAI PESISIR - Ritawiyati Ritawiyati; Sri Maryanti; Muhammad Thamrin (Program Studi Pendidikan Ekonomi Universitas Riau, 2018)
The purpose of the research is to find out the break even point as profit planning, asfor the type and source of data using secondary data, secondary data can beobtained from records about costs, sales, through documents owned by fruit juicefarmer groups. Mathematically using both units in Rupiah and in Units. Based ondata analysis carried out on fruit juice farmer groups in Lembah sari village, RumbaiPesisir sub-district, the conclusion is that determining break even point (BEP) foreach company, including small industries is one of the plans that need to be done bybusiness owners. to reach the break-even point of sale in rupiah, the production ofsweet potato crackers in the fruit juice farmer group must be able to sell the productof the product equal to Rp. 19,647,000 in each month or more than the sale. And toreach the unit that can be sold so that the sweet potato cracker in the fruit juicegroup does not suffer losses, it must be able to sell 767 kg per month.